2014
DOI: 10.1038/jp.2014.173
|View full text |Cite
|
Sign up to set email alerts
|

Intra-vaginal prostaglandin E2 versus double-balloon catheter for labor induction in term oligohydramnios

Abstract: Intravaginal PGE2 and double-balloon catheter are comparable methods for cervical ripening in term pregnancies with oligohydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Figure summarised the identification and selection process. Of the 152 studies, nine articles were included in the systematic review and meta‐analysis . Details of the characteristics of the included individual studies are demonstrated in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure summarised the identification and selection process. Of the 152 studies, nine articles were included in the systematic review and meta‐analysis . Details of the characteristics of the included individual studies are demonstrated in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria varied across the records, some studies included only the primiparous, whereas others recruited those who were primiparous or multiparous. Several studies excluded women with twin pregnancy, pre‐eclampsia, oligohydramnios, or history of caesarean section; others did not exclude them . In addition, there were differences between studies with regard to the minimal gestational ages and maximal Bishop scores used for inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, no differences in cesarean delivery rates have been reported in studies comparing prostaglandin E2 and mechanical dilation in women with oligohydramnios. 8, 9 A previous meta-analysis found that misoprostol was associated with an increased risk of tachysystole compared with prostaglandin E2. 5 Because oligohydramnios is associated with increased risk of fetal heart rate decelerations during labor 1, 2, 6 , a hypothetical concern is an increased risk of cesarean delivery in women undergoing induction of labor with misoprostol.…”
Section: Commentmentioning
confidence: 99%
“…3 Misoprostol (prostaglandin E1) is an effective induction agent when the cervix is not favorable. 4 Although maternal and neonatal outcomes related to prostaglandin E2 use in women with oligohydramnios have been studied, 8, 9 limited data are available regarding misoprostol for induction of labor in the setting of oligohydramnios. Misoprostol is associated with tachysystole with or without fetal heart rate changes compared with prostaglandin E2 and oxytocin.…”
Section: Introductionmentioning
confidence: 99%
“…Cervix priming with mechanical methods for term pregnancy with unfavorable cervix has been demonstrated to be as effective as priming with prostaglandins but associated with less adverse effects. 2,3 Compared to pharmacological agents, mechanical methods have fewer systemic effects and are associated with lower rates of tachysystole; they have a lower cost and do not require specific conditions of storage and refrigeration. 4 However, the introduction of mechanical methods may contribute to maternal discomfort and have been associated with a potential risk of maternal and neonatal infection.…”
Section: Introductionmentioning
confidence: 99%